DETERMINAN RETURN ON ASSET (ROA) PADA INDUSTRI PERBANKAN SYARIAH DI INDONESIA PERIODE 2010-2018: PENDEKATAN AUTOREGRESSIVE DISTRIBUTED LAG (ARDL) - Feranti Farah Nur; Raditya Sukmana (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
This research aimed to test and analyze the influences of Non Performing Financing (NPF), Capital Adequacy Ratio (CAR), and Operational Cost of Operational Income (BOPO) on Return on Asset (ROA) in Sharia Banking Industry Indonesia period 2010-2018. It used quantitative approach. Furthermore, data analysis technique used was Autogressive Distributed Lag (ARDL). The results of this research showed that in a long-term, NPF and BOPO variables had a negative and significant effect on the variable of Return on Asset (ROA), and the variable of CAR had a positive and insignificant on the variable of Return on Asset (ROA). Meanwhile, in a short-term, NPF and BOPO variables had a negative and significant effect on the variable of Return on Asset (ROA), and the variable of CAR had a positive and significant effect on the variable of Return on Asset (ROA).Keywords: Islamic Banks, Return on Asset, Non Performing Financing, Capital Adequacy Ratio, Operational Cost of Operational Income, Autoregressive Distributed LagREFERENCES Arifin, Zainul. 2002. Dasar-Dasar Manajemen Bank Syariah. Bandung: Alfabeta.Athanasoglou, Panayiotis, et al. 2005. Bank-Specific, Industry-Specific and Macroeconomic Determinants of Bank Profitability. MPRA Paper No. 32026, 4-35. Dendawijaya, Lukman. 2003. Manajemen Perbankan. Jakarta: Ghalia Indonesia.Ekananda, Mahyus. 2014. Analisis Data Time Series: untuk Penelitian Ekonomi, Manajemen dan Akuntansi. Jakarta: Mitra Wacana Media.Ekananda, Mahyus. 2015. Ekonometrika Dasar: untuk Penelitian Ekonomi, Sosial dan Bisnis. Jakarta: Mitra Wacana Media.Haron, Sudin. 2004. Determinant of Islamic Bank Profitability. Working Paper Series No. 002, Global Journal of Finance and Economics, 1(1), 1-22.IIsmail. 2011. Perbankan Syariah. Jakarta: Kencana Prenada Media.Kasmir. 2013. Analisis Laporan Keuangan. Jakarta: PT Raja Grafindo Persada.Muhamad. 2002. Manajemen Bank Syariah. Yogyakarta: UPP AMP YKPN.Pesaran, M. Hashem, et al. 1999. Bounds Testing Approaches to the Analysis of Level Relationships. Journal of Applied Econometrics, (16), 289-326.Pesaran, M. Hashem, et al. 2001. Bounds Testing Approaches to the Analysis of Long Run Relationships. Trinity College, Cambridge.Ramlall, I. 2009. Bank-Specific, Industry-Specific and Macroeconomic Determinants of Profitability in Taiwanese Banking System: Under Panel Data Estimation. International Research Journal of Finance and Economics, (34), 160-167.Umam, Khotibul. 2016. Perbankan Syariah: Dasar-Dasar dan Dinamika Perkembangannya di Indonesia. Jakarta: PT Raja Grafindo Persada.Usman, Rachmadi. 2012. Aspek Hukum Perbankan Syariah. Jakarta: Sinar Grafika.Wasiuzzaman, Shaista and Hanimas Ayu Bt Ahmad Tarmizi. 2014. Profitability of Islamic Banks in Malaysia: An Empirical Analysis. Journal of Islamic Economics, Banking and Finance, 6(4), 53-68.Zawadi, Ally. 2014. Determinants of Banks Profitability in a Developing Economy: Empirical Evidence from Tanzania. European Journal of Business and Management, 6(31), 363-375.